Workers at Risk : Panel Data Evidence on the COVID-19 Labor Market Crisis in India - Bussolo, Maurizio; Kotia, Ananya; Sharma, Siddharth (World Bank, Washington, DC, 2021)
The COVID-19 pandemic is having unequal impacts. Research has highlighted that across race, gender, age, and income groups, the health and economic consequences of this crisis are far from uniform and other preexisting inequalities have been exacerbated. This paper focuses on the differential impact on the formal and informal segments of the labor market in India, using data from a large household panel survey and employing a difference-in-differences event study approach. Within the same industry and district, initially informal wage workers were significantly more vulnerable to the loss of employment than initially formal workers during the early phase of COVID-19 (April 2020). Furthermore, income declined significantly more for households whose head worked as an informal wage worker than for households with a formally employed head. However, the post-COVID employment and income differentials between informal and formal workers narrowed after April 2020. By July 2020, the decline in income (from the pre-COVID baseline of February 2020) was not significantly different across households with informally and formally employed heads, suggesting that while informal workers were affected more severely by the early COVID-19 shock, they also recovered faster from it.